Design of mechanical flower rack / Muhammad Abdul Rahman Muhamad Malek - Muhamad Malek, Muhammad Abdul Rahman (2024)
The Design of Mechanical Flower Rack project is an innovative and sustainable solution for plant enthusiasts. This project main objective is to create a functional and visually appealing flower rack that incorporates mechanical elements and prioritizes the use of eco-friendly materials. Next, to minimize environmental impact while providing a practical solution for plant enthusiasts. The lack of sustainable and innovative flower racks available on the market is the main problem statement of this project. Most flower racks are made of non-eco-friendly materials and lack mechanical elements, making it challenging to hold a variety of plants and flowers. It is applicable to using various methodologies, including research, brainstorming, prototyping, and testing. Sustainable engineering and design principles will guide the team's decisions throughout the project's development. The functional, durable, and visually appealing flower rack that can hold a variety of plants and flowers, while also minimizing environmental impact. The project's significance lies in its contribution to sustainable engineering and design, providing a practical solution for plant enthusiasts, and inspiring future designs in the field. Finally, this project had been successfully produced and proven to be able to provide a positive impact to users for their necessary in daily use .